The Rejuvenation of Industrial Policy - Stiglitz, Joseph E.; Lin, Justin Yifu; Monga, Célestin (World Bank, Washington, DC, 2014)
This essay is about an important area in which there has been major rethinking -- industrial policy, by which the authors mean government policies directed at affecting the economic structure of the economy. The standard argument was that markets were efficient, so there was no need for government to intervene either in the allocation of resources across sectors or in the choices of technique. And even if markets were not efficient, governments were not likely to improve matters. But the 2008-2009 global financial crisis showed that markets were not necessarily efficient and, indeed, there was a broad consensus that without strong government intervention -- which included providing lifelines to certain firms and certain industries -- the market economies of the United States and Europe may have collapsed. Today, the relevance and pertinence of industrial policies are acknowledged by mainstream economists and political leaders from all sides of the ideological spectrum. But what exactly is industrial policy? Why has it raised so much controversy and confusion? What is the compelling new rationale that seems to bring mainstream economists to acknowledge the crucial importance of industrial policy and revisit some of the fundamental assumptions of economic theory and economic development? How can industrial policy be designed to avoid the pitfalls of some of the seeming past failures and to emulate some of the past successes? What are the contours of the emerging consensus and remaining issues and open questions? The paper addresses these questions.